Medaliony przeciw milczeniu. Michał Głowiński: Carska filiżanka. Szesnaście opowieści. Warszawa, Wielka Litera, 2016, ss. 238 - Tomczok, Marta (Narracje o Zagładzie [czasopismo zamknięte], 2016)
Medallions against Silence. Michał Głowiński: Carska filiżanka. Szesnaście opowieści. Warszawa, Wielka Litera, 2016, ss. 238. The author of the review is interested in chosen questions appearing in the collection of sixteen stories by Michał Głowiński, entitled Carska filiżanka… These include: memory and oblivion, silence and speaking, fate, past, old age, and homoerotism. While discussing the particular parts of the book, the author points to its most important and complex issue – homoerotism. Next to the war and its traces vanishing in old memory, it seems to be the most mature and interestingly formulated subject matter of the collection. The author does not abandon the autobiographical reading of Głowiński’s work, but she proposes that one can observe it through the prism of the category of the medallion, described by the writer in one of his works in literary studies. In this way, Marta Tomczok finds new realisations of the literary form known from Zofia Nałkowska’sand Ludwik Hering’s works, filled with a historical reality which is completely different from one of the war. The author also stresses the element linking the mentioned medallions: the crystal clear language.